Tourism and economic growth in Portugal: an empirical investigation of causal links - João Paulo Cerdeira Bento (Tourism & Management Studies)
This study uses quarterly time series for the period from 1995 to 2015 to assess the temporal causal link between tourism and economic growth based on the hypothesis according to which tourism development precedes economic growth. It adopts a disaggregated approach to study the effects of both domestic tourists and foreign tourists on economic growth. Seasonally adjusted tourist arrivals are used to represent tourism activity. This study employs time series cointegration methods that are capable of accommodating structural breaks. The results show that the Portuguese case supports the tourism-led growth hypothesis. There is evidence of a long run cointegration relationship between the real gross domestic product and arrivals at tourist’s accommodation establishments of both domestic tourists and foreign tourists. Long run unidirectional Granger causality exists running from domestic tourists to real gross domestic product, but not vice versa. The findings indicate that domestic tourism promotes economic growth. The main policy implication is that policy makers should contribute to tourism development and encourage tourism opportunities in domestic markets by targeting not only foreign tourists, but also domestic tourists to ensure the longterm success and strategic planning of the tourism sector in Portugal.